Public Perceptions of Family Presence During Resuscitation: A Cross-Sectional Survey in Slovenia - DUJC Ines; ŽVANUT Boštjan; KARNJUŠ Igor (Slovenian Journal of Public Health)
In Slovenia, the practice of having family present during resuscitation (FPDR) in the clinical setting is still controversial. Therefore, the aim of the study was to explore current public perceptions regarding FPDR in Slovenia and to investigate whether demographic characteristics are related to these perceptions.